RESPON BAYAM BRAZIL (Alternanthera sissoo) PADA APLIKASI SUMBER CAHAYA BUATAN DENGAN MEDIA PUPUK KANDANG KAMBING DAN KOMPOS Eichhornia crassipes - Yohana Theresia Maria Astuti; Agri Fadhlillah Sukma Armanda; Candra Ginting (Jurnal Penelitian Pertanian Terapan, 2023)
The study aimed to determine the response of Brazilian spinach plants to the application of water hyacinth (Eichhornia crassipes) compost and goat manure with LED and fluorescent artificial light. The research was conducted at KP2 Instiper in Maguwoharjo, Depok, Sleman from April to June 2022. The research used an experimental method with a split-plot design. The main plot in the form of artificial light consists of 3 types, namely: Control (sunlight), 18 Watt Neon Lights, and 36 Watt LED Lights. The subplots consisted of 3 types of organic fertilizers, namely: Control (without fertilizer), water hyacinth compost, and goat manure compost, so 3 x 3 = 9 treatment combinations were obtained, each with 3 replications. Based on the results of the research conducted, it can be concluded that the combination of various light sources and various organic fertilizers affects the growth of Brazilian spinach (Alternanthera sissoo). The growth and biomass of Brazilian spinach in a combination of sunlight and 36 Watt LED lights with water hyacinth compost and goat manure was better than the growth and biomass of Brazilian spinach in a combination of 18 Watt fluorescent lights with various kinds of organic fertilizers. There is a positive correlation between the crown and root biomass. Sunlight and LED have a light intensity that is more suitable for the growth of Brazilian spinach compared to fluorescent lamps.